Immunotherapy-based salvage therapy in advanced soft tissue sarcoma after first-line chemotherapy: a retrospective single-center analysis with emphasis on undifferentiated pleomorphic sarcoma - Zhichao Liao; Junbo Huang; Haotian Liu; Chao Zhang; Ting Li; Hongyu Wang; Yuanxin Liu; Sijia Ren; Zhiwu Ren; Haixiao Wu; Ruwei Xing; Sheng Teng; et al. (Frontiers in Immunology, 2026)
Introduction Soft tissue sarcomas (STS) are rare mesenchymal malignancies with limited treatment options in advanced stages. Anthracycline-based chemotherapy remains the standard of care but yields modest outcomes with significant toxicity, underscoring the need for more effective strategies. Methods We retrospectively analyzed 56 patients with advanced STS who received PD-1 inhibitor-based therapy at Tianjin Medical University Cancer Institute and Hospital between January 2021 and January 2026. Treatment regimens included immunotherapy alone or in combination with chemotherapy or targeted therapy. The observed primary endpoints were median progression-free survival (mPFS) and median overall survival (mOS). Survival outcomes were analyzed by Kaplan–Meier analysis; factors associated with prognosis were identified by a Cox proportional hazards regression model. Outcomes were compared with a historical cohort of 53 patients treated with chemotherapy alone. Results A total of 56 patients were included, and the median follow-up time in the immunotherapy cohort was 19.2 months (range, 1.32–52.8 months). Patients with UPS had a longer median PFS than those with non-UPS histology (P = 0.045). Patients receiving immunotherapy combined with chemotherapy had longer median PFS (P = 0.047) and median OS (P = 0.046) compared with those receiving immunotherapy without chemotherapy. Multivariable Cox regression identified UPS histology (P = 0.023) and immunotherapy combined with chemotherapy (P = 0.047) as factors associated with PFS in advanced STS. Compared with 53 patients who received chemotherapy alone, the immunotherapy-based comprehensive treatment group had longer median PFS in the overall population (P = 0.023); the pure chemoimmunotherapy group (n = 22) also showed longer PFS (P = 0.014). This association was also observed in the UPS subgroup (P = 0.006). Treatment-related adverse events were predominantly grade 1–2; no grade 4–5 severe adverse events or treatment-related deaths occurred. Discussion Immunotherapy-based regimens, particularly chemoimmunotherapy, showed a suggested PFS benefit over conventional chemotherapy in advanced STS, with UPS showing a suggested association with disease control. The safety profile was acceptable. Nevertheless, the limitations inherent to the retrospective design, historical controls, modest sample size, and immature overall survival data warrant cautious interpretation.